A TWO YEAR REVIEW OF UTERINE RUPTURE AT GYNAECOLOGY ’˜A’ UNIT AYUB TEACHING HOSPITAL - Alam, Iqbal; Khan, Alam; Ahmed, Roshina; Begum, Nazakat (Journal of Ayub Medical College Abbottabad, 2000)
Background: Uterine rupture is a grave obstetrical problem, particularly in the developing world. Despite the improvement in the obstetrical procedures such as classic caesarean section, internal version, total breech extraction etc. the incidence of rupture remains high. Mainly due to the use of oxytocic drugs by people not qualified for their use. Methods: We conducted a retrospective study of 27 proven cases of ruptured uterus in Gynae ’A: unit of Ayub Teaching Hospital, between 1997-1998. These cases were analysed with regard to their clinical presentation, past history’, complications, management and outcome. Results: The incidence of uterine rupture was 1.14%. The commonest antecedent factor was use of oxytocic drugs by unskilled or semiskilled persons. The major clinical presentation was with symptoms suggestive of shock. Subtotal abdominal hysterectomy was performed in 62.9% of cases. Repair of uterus with or without bilateral tubal ligation was done in 37.1% of cases. There were no maternal deaths.